Human use of birds and fish in marine settings of southern Patagonia and Tierra del Fuego in the Holocene: A first macro-regional approach - Zangrando, Atilio Francisco Javier (2015)
This paper presents a review of the zooarchaeological representations of birds and fish in coastal archaeological sites of southern Patagonia and Tierra del Fuego (47°-55°S). The spatial and temporal variations of this faunal record are assessed in order to understand their contribution in human subsistence in different geographic and cultural settings between 6500 and 100BP. Spatially, the importance of birds and fish in human subsistence was similar between the Pacific and Atlantic coasts along the Holocene, although differences in taxonomic compositions of bird bone assemblages are observed among regions. Temporally, the analysis suggests an increase in bird hunting in the considered area in the last 3000 years, while an intensification of fishing activities can be proposed for the archipelagic area for that time period.